2017
DOI: 10.1111/cgf.13268
|View full text |Cite
|
Sign up to set email alerts
|

Rib‐reinforced Shell Structure

Abstract: Figure 1: We present a computational framework to generate ribs to enhance the structural strength and stiffness of a shell (a). Our ribreinforced shell structure (c) costs the same amount of material as a pure shell without any ribs (a), while achieving much better mechanical performance. And (b) and (d) are coloring visualizations of the magnitude of von Mises stress of (a) and (c), respectively, under the same load and boundary conditions. Warmer color represents higher stress and red encodes stress exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…This principle has been applied to 2D planes (e.g. [17]) and curved surfaces [18], [19], [20]. The appealing 2D results are achieved by tracing stress directions or based on a ground structure approach [21], [22].…”
Section: Structural Optimization For 3d Printingmentioning
confidence: 99%
“…This principle has been applied to 2D planes (e.g. [17]) and curved surfaces [18], [19], [20]. The appealing 2D results are achieved by tracing stress directions or based on a ground structure approach [21], [22].…”
Section: Structural Optimization For 3d Printingmentioning
confidence: 99%
“…The material consumption of honeycomb-like 3D models is reduced via a hollowing optimization algorithm in [17]. Stiffened objects were first investigated in [18]. A method to produce optimized structures for any input surface with any load configurations was researched in [22].…”
Section: Related Workmentioning
confidence: 99%
“…Li W. et al (2017) proposed the rib reinforcement as a way to enhance the shell structures (Li et al , 2017) as shown in Figure 18 (Figure 19). The technology was proposed for AM so that the reinforcements do not require additional material because it is extracted from the thickness of the shell.…”
Section: Latest Development and Applicationsmentioning
confidence: 99%